Research on the Cutting Force and Serrated Chips in Ultra-Precision Micro-Grooving of SLM Ti6Al4V Alloy - Zhongpeng Zheng; Jiajing Guo; Ruilin Gao; Xin Jin (Micromachines, 2023)
Selective laser melting (SLM) has significant advantages in the near net shape manufacturing of metal parts with complex geometries. However, SLM parts usually have problems such as poor surface quality and low dimensional accuracy, which require post-processing. This paper focuses on the research around the influence of ultra-precision micro-grooving the SLM Ti6Al4V alloy on the cutting force and serrated chips. The influence of the processing parameters on the cutting force and surface processing quality was analyzed in detail, and the cutting simulation model of the SLM Ti6Al4V alloy was established. The formation process of the serrated chip was successfully simulated, and the experiments verified the reliability of the established model. The research results show that the dynamic cutting force and surface processing quality are mainly related to the depth of cut, and the two trends are consistent. It is also shown that the serrated chip begins on the free surface of the workpiece and propagates deeply in the shear zone, forming a shear band, and its serrated nodules move upward and forward to form periodic serrated chips.